1991
DOI: 10.1021/ja00003a048
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of C-terminal serine and threonine extended precursors into C-terminal .alpha.-amidated peptides: a possible chemical model for the .alpha.-amidating action of pituitary enzymes

Abstract: The primary amide functionality present at the carboxyl terminus in the majority of polypeptide hormones and in many bioactive neuropeptides1 is known2 to be derived from a glycine (Gly) residue at the C-terminus of their Gly extended precursors.3We present here a practical, in vitro model for the terminal amidation reaction using either a serine (Ser) or threonine (Thr)4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…It was shown that the pH value is of particular importance for a successful and selective oxidation. 73,83 Furthermore, Griffith was able to show that cyclohexane can be used as an environmentally friendly solvent substitute for the toxic tetrachloromethane. 84 Most RuO 4 -catalyzed oxidations, however, suffer from the necessity of employing stoichiometric amounts of an oxidizing salt, which causes problems especially on large-scale reactions.…”
Section: Fragmentation Of Alkenesmentioning
confidence: 99%
“…It was shown that the pH value is of particular importance for a successful and selective oxidation. 73,83 Furthermore, Griffith was able to show that cyclohexane can be used as an environmentally friendly solvent substitute for the toxic tetrachloromethane. 84 Most RuO 4 -catalyzed oxidations, however, suffer from the necessity of employing stoichiometric amounts of an oxidizing salt, which causes problems especially on large-scale reactions.…”
Section: Fragmentation Of Alkenesmentioning
confidence: 99%
“…On the basis of the similarities between the peptidylglycine aamidating and dopamine /J-hydroxylation reactions with respect to the cofactors required and the hydroxylated product, it has been suggested that the a-amidation is a mono-oxygenase reaction [4]. However, as has been pointed out by some investigators [21,22], two different mechanisms can be considered for the peptidylglycine a-hydroxylation, as illustrated in Scheme 1: direct mono-oxygenation at the glycine a-C atom to yield a carbinolamide (peptidylglycine ac-hydroxyglycine, II) (pathway A), which subsequently dissociates to the products (IV and V), or dehydrogenation leading to an imine (III), followed by hydration, resulting in the same carbinolamide (pathway B). Pathway A corresponds to a typical mono-oxygenase reaction, whereas pathway B corresponds to an oxidase reaction involving tandem dehydrogenation of one substrate and one auxiliary reductant [21].…”
Section: Introductionmentioning
confidence: 99%
“…Ranganathan reported selective catalytic peptide backbone cleavage at serine and threonine residues through RuCl 3 /NaIO 4 oxidation (Fig. 21) [160,161]. This facile C-N bond cleavage was induced by oxidative scission of the Cβ-Cα bond at Ser/Thr side-chains, involving either a cyclic (25) Because of the high reactivity of Ru(VIII) oxo species, other amino acid (e.g., Tyr, Trp, Cys, and Met) residues were also oxidized or decomposed under these reaction conditions.…”
Section: Oxidative Cleavage Assisted By Metal Ions/metal Complexesmentioning
confidence: 99%